Ethics : - MacKinnon, Barbara (Wadsworth Pub. Co., 1995)
Contents: Ethics and ethical reasoning; Ethical relativism; Egoism; Utilitarianism; Kant's moral theory; Natural law and natural rights; Virtue ethics...